Pre-pubertal exposure to ibuprofen impairs sperm parameters in male adult rats and compromises the next generation - Barbosa, Mariana Gazoli [UNESP]; Jorge, Bárbara Campos [UNESP]; Stein, Julia [UNESP]; Santos Ferreira, Dayana Agnes [UNESP]; Barreto, Ana Carolina da Silva [UNESP]; Reis, Ana Carolina Casali [UNESP]; Moreira, Suyane Da Silva [UNESP]; Inocencio, Leonardo Cesar De Lima [UNESP]; Macorini, Luis Fernando Benitez; Arena, Arielle Cristina [UNESP] (Taylor & Francis, 2020)
Ibuprofen is one of the most commonly prescribed anti-inflammatory drugs in pediatric practice. This drug inhibits the cyclooxygenase enzyme, reducing the production of prostaglandin, an important mediator on male reproductive function. We examined if pre-pubertal treatment with ibuprofen in male rats can affect the reproductive parameters of these animals in adult life and on their descendants. Male rats (23 days old) received ibuprofen (0; 2.4; 7.2 or 14.3 mg/kg/day), per gavage, from postnatal day (PND) 23 to 53. At sexual maturity, treated males were placed with untreated females for obtaining the next generation (F1). The highest dose of ibuprofen interfered in sexual behavior and reduced the fertility potential of these animals in adulthood. Additionally, the ibuprofen treatment altered the sperm quantity and quality, as evidenced by a decrease in sperm motility and in the daily sperm production in the testis. Testosterone levels were also reduced by pre-pubertal treatment. The paternal treatment with this drug also influenced the reproductive outcomes of progeny. The male offspring from males treated exhibited acceleration in sperm transit time in the epididymis and the number and volume of Leydig cell nuclei were decreased, while the estrous cyclicity was displayed and the fertility potential reduced in the female offspring. The pre-pubertal ibuprofen-treatment caused negative reproductive impacts in adulthood, compromising sperm quality and quantity, as well as interfered in the reproductive outcomes of the next generation.
Keywords: multigenerational effects; Non-steroidal anti-inflammatory; peripuberty; prostaglandin; sperm